Pengaruh Kualitas Produk, Harga dan Kesadaran Merek Terhadap Kepuasan Konsumen - Suci Suci; Annur Fitri Hayati (Universitas Negeri Padang, 2023)
The purpose of this study was to determine the effect of product quality, price and brand awareness on consumer satisfaction at Makjus Cake shop consumers in Padang City. The number of research samples was determined based on the William Cochran formula, as many as 97 people and selected using the Purposive Sampling technique. The data used is the type of primary data obtained through the distribution of questionnaires to the people of Padang City with predetermined criteria. The analytical method used is multiple linear regression using SPSS version 21. The results of this study indicate that (1) product quality, price and brand awareness have a significant effect on consumer satisfaction at Makjus Cake shop consumers in Padang City, (2) product quality has a significant effect on consumer satisfaction. consumer satisfaction at Makjus Cake shop consumers in Padang City, (3) price has a significant effect on consumer satisfaction at Makjus Cake shop consumers in Padang City, (4) brand awareness has a significant effect on consumer satisfaction at Makjus Cake shop consumers in Padang City.